2015
DOI: 10.1039/c4tc02576h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spacer length and rigidity on properties of phosphonium polymers and on their supramolecular assembly with a conjugated polyelectrolyte

Abstract: A series of seven cationic polymers have been prepared wherein the length of spacer between charge-bearing sites has been varied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Compared with traditional organic frameworks, ionic hypercrosslinked polymers, specifically those involving ionic liquids as monomers, have attracted growing attention. These materials can possess good thermal and chemical stability, properties that can be tuned upon simple counterion exchange, and which can readily form layer‐by‐layer self‐assembled films with other ionic polymers . For example, Yang et al reported an alkaline anion exchange membrane R1 (Scheme ) comprised of copolymerized imidazolium‐functionalized ionic liquids with styrene and acrylonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional organic frameworks, ionic hypercrosslinked polymers, specifically those involving ionic liquids as monomers, have attracted growing attention. These materials can possess good thermal and chemical stability, properties that can be tuned upon simple counterion exchange, and which can readily form layer‐by‐layer self‐assembled films with other ionic polymers . For example, Yang et al reported an alkaline anion exchange membrane R1 (Scheme ) comprised of copolymerized imidazolium‐functionalized ionic liquids with styrene and acrylonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…When visible‐absorbing PELs (Chart ) are employed, the LbL films can be used as finely tuned optical or optoelectronic components . A detailed study on LbL behavior of the LX series polymers (Chart ) and Pc12‐100 confirmed that the spacer flexibility and distance between phosphonium charge bearing units have significant effect on the properties of the PEL and LbL films with polyanions …”
Section: Introductionmentioning
confidence: 96%
“…An example in which chemical stability is paramount is in an alkaline fuel cell, where the membrane must tolerate extended heating at temperatures up to 80 °C in the presence of aqueous hydroxide. The PEL R3 has proven stable enough for test devices under such conditions, and recent advances in the preparation of tetraarylphosphonium polymers suggest that more advances are on the horizon in this area as structural elements leading to improved stability are identified. PELs also offer advantages in medicinal contexts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations